How do you identify patients with nonalcoholic fatty liver disease who have progressed to nonalcoholic steatohepatitis?. Issue 2 (February 2018) - Naing, Kyaw; Wright, Alex
Abstract : EVIDENCE‐BASED ANSWER : Ultrasound is useful for finding patients with high degrees of steatosis at risk for nonalcoholic steatohepatitis (NASH), but is less useful for finding nonalcoholic fatty liver disease (NAFLD) if steatosis involves less than 30% of the liver. Magnetic resonance imaging (MRI) performs better than ultrasound if steatosis is less than 25% but more than 10%. Alanine transaminase (ALT) levels are poor predictors of the presence of NASH (SOR: C, systematic review of RCTs and observational studies and metaanalysis of diagnostic cohort studies). After excluding other causes of liver disease, the NAFLD Fibrosis Score is useful for determining which patients may need a biopsy to evaluate for NASH (SOR: C, expert opinion).